ESTIMASI KEBUTUHAN LAHAN PEMAKAMAN DI KOTA BANDA ACEH - Farhan, Nubuwat (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2016)
The purpose of this research is to estimate the needs of burial grounds, factors affecting land requirements in the form of total population, mortality and economic growth. This study uses primary data from interviews and secondary data. The sample in this study were 100 respondents by 9 districts of Banda Aceh. The analysis model is descriptive and qualitative analysis. The analysis showed that 57 percent of them chose to be buried in Banda Aceh. 23 percent have a private burial grounds and 20 percent chose to be buried in their homeland. Based on this study of limited land led to the need for special attention from the government of Banda Aceh to seek provision of burial grounds outside the district of Banda Aceh, particularly the public cemetery of Banda Aceh.Â Keywords: Population, Mortality, Growth, Qualitative Descriptive Analysis.Â